2000
DOI: 10.1097/00000542-200006000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Acute Severe Isovolemic Anemia Impairs Cognitive Function and Memory in Humans

Abstract: Acute reduction of hemoglobin concentration to 7 g/dl does not produce detectable changes in human cognitive function. Further reduction of hemoglobin level to 6 and 5 g/dl produces subtle, reversible increases in reaction time and impaired immediate and delayed memory. These are the first prospective data to demonstrate subtle degraded human function with acute anemia of hemoglobin concentrations of 6 and 5 g/dl. This reversibility of these decrements with erythrocyte transfusion suggests that our model can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
132
0
18

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(156 citation statements)
references
References 0 publications
6
132
0
18
Order By: Relevance
“…Firstly, the lowest score of WCPTS is 7, and the corresponding Hb level of 7 g/dl has been proved to be adequate in health human (1). According to Weiskopf's report (12), Hb concentrations of ≤ 6 g/dl could only produce reversible subtle impairment of human function in health volunteers without other impairment of organs, so that most of the patients undergoing elective surgery could bear Hb level of 6-7 g/dl based on Weiskopf's study theoretically, and this is supported by ASA guideline for RBCs transfusion (3) that "RBCs should usually administered when Hb concentration is less than 6 g/dl". Therefore, the initial score of WCPTS could be decreased to 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the lowest score of WCPTS is 7, and the corresponding Hb level of 7 g/dl has been proved to be adequate in health human (1). According to Weiskopf's report (12), Hb concentrations of ≤ 6 g/dl could only produce reversible subtle impairment of human function in health volunteers without other impairment of organs, so that most of the patients undergoing elective surgery could bear Hb level of 6-7 g/dl based on Weiskopf's study theoretically, and this is supported by ASA guideline for RBCs transfusion (3) that "RBCs should usually administered when Hb concentration is less than 6 g/dl". Therefore, the initial score of WCPTS could be decreased to 6.…”
Section: Discussionmentioning
confidence: 99%
“…Decision of administration of fresh frozen plasma (FFP), platelet, cryoprecipitate, or other blood products was made by attending anesthesiologists or surgeons according to their own experience without restriction. Research nurses who were not involved in study implementation and were unaware of studygroup assignments telephoned patients or proxies closely at 4,8,12,16,20, and 26 weeks after hospital discharge. They spoke directly to patients who were accessible by telephone or to proxies if patients were dead or could not talk on telephone.…”
Section: Treatment Assignment and Follow-upmentioning
confidence: 99%
“…Cognitive function and memory are usually affected at 6 g per 100 ml but can be partially corrected with supplemental oxygen. 45,46 Electrocardiographic changes occurred in only 5% of normal volunteers at Hb of 5 g per 100 ml. 47 A 1988 case-control study of surgical patients refusing blood transfusion found a 61.5% mortality with preoperative Hb o6.0 g per 100 ml.…”
Section: Rbc Transfusion In Stem Cell Transplantationmentioning
confidence: 97%
“…23 Inadequate brain oxygen delivery may be responsible for the observed decline in cognitive function during severe anemia. 30 In surgical patients, low admission and discharge Hb levels have also been associated with increased postoperative mortality, increased major adverse cardiovascular events, increased length of hospital stay, readmission, reduced quality of life, and impaired functional recovery. 1,27,[31][32][33] Risk of therapies that impair the cardiovascular responses to anemia (b-blockade)…”
Section: The Risk Of Preoperative Anemiamentioning
confidence: 99%